Analysis of Thyristor based dual converter controlling the firing angle for HVDC transmission - Hassan, Mohammed Fuad; Monir, K. M. Mahmudul; Hossain, Md. Ismail; Joy, Sudipto Das (BARC University, 2018)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2017.